MicroRNAs activate gene transcription epigenetically as an enhancer trigger. Issue 10 (3rd October 2017) - Xiao, Min; Li, Jin; Li, Wei; Wang, Yu; Wu, Feizhen; Xi, Yanping; Zhang, Lan; Ding, Chao; Luo, Huaibing; Li, Yan; Peng, Lina; Zhao, Liping; et al.
ABSTRACT: MicroRNAs (miRNAs) are small non-coding RNAs that function as negative gene expression regulators. Emerging evidence shows that, except for function in the cytoplasm, miRNAs are also present in the nucleus. However, the functional significance of nuclear miRNAs remains largely undetermined. By screening miRNA database, we have identified a subset of miRNA that functions as enhancer regulators. Here, we found a set of miRNAs show gene-activation function. We focused on miR-24-1 and found that this miRNA unconventionally activates gene transcription by targeting enhancers. Consistently, the activation was completely abolished when the enhancer sequence was deleted by TALEN. Furthermore, we found that miR-24-1 activates enhancer RNA (eRNA) expression, alters histone modification, and increases the enrichment of p300 and RNA Pol II at the enhancer locus. Our results demonstrate a novel mechanism of miRNA as an enhancer trigger.